2005
DOI: 10.1108/14636646200500009
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for managing self‐harm in a forensic setting

Abstract: Previous research has established that guidelines to facilitate a non‐judgemental, consistent approach to self‐harm management would be useful to staff working in a forensic psychiatric setting. In the preparation of these guidelines, a literature search was conducted to examine the evidence on clinical effectiveness for managing self‐harm. Overall, the evidence for defining a definitive treatment approach to self‐harm is extremely limited. However, a number of studies/reviews have identified aspects of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It is becoming a common knowledge among practitioners that secure environments are hotbeds for self-harming behaviours [3]. Similar outcomes are reflected in this study as participants reported that some users only commence acts of harm when detained in forensic mental health settings.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is becoming a common knowledge among practitioners that secure environments are hotbeds for self-harming behaviours [3]. Similar outcomes are reflected in this study as participants reported that some users only commence acts of harm when detained in forensic mental health settings.…”
Section: Discussionsupporting
confidence: 72%
“…Secure hospitals are places with the highest incidence of self-injury in both female and male service users [3]. Most psychiatric nurses in these hospitals have little understanding of self-harm [4].…”
Section: Introductionmentioning
confidence: 99%
“…Staff rated their understanding of NSSI as 44%. Understanding increased with training Gough (2005) United Kingdom Results from Gough & Hawkins (2000) 12 Guidelines were suggested for forensic psychiatric service staff for dealing with NSSI Heney (2007) Canada N = 85; n = 44 female inmates, n = 41 members of security 97% of inmates that engaged in NSSI said segregation was an inappropriate response after NSSI, they perceived it as a punishment; 78% of inmates said females who engage in NSSI need to talk to someone after. The majority said they want to self-injure in situations of helplessness, powerlessness, or isolation Ireland & Quinn (2007) United Kingdom N = 162 prison officers in training (38.27%…”
Section: Discussionmentioning
confidence: 98%
“…Although the majority of staff surveyed reported having support in the treatment of NSSI, only half of the staff characterized the quality of support as representing "best practice" (Marzano & Adler, 2007). Further, despite the development of guidelines (e.g., Gough, 2005) and handbooks (e.g., Pengelly, Ford, Blenkiron, & Reilly, 2008) to help staff understand and manage NSSI, it is unknown whether these are frequently implemented.…”
Section: Complicating Factorsmentioning
confidence: 89%
“…). Secure environments have the highest incidence of self‐harm (Gough ; Tantam & Huband ). But the statistics indicating this are likely to be an underestimate, as the majority of cases of self‐harm usually remain a secretive act that can go on for a long time without being discovered (Mental Health Foundation ).…”
Section: Introductionmentioning
confidence: 99%